Applying lean methodology to improve parenteral chemotherapy and monoclonal antibody documentation processes based on Normalisation Process Theory. Issue 1 (2nd January 2017) - West, Lorna Marie; Brincat, Alison; Mercieca, Mark; Fsadni, Demis; Rapa, Ian; Cordina, Maria
Abstract : Objective: To determine the impact of lean thinking on the original time required to prepare the necessary documentation in relation to the preparation of parenteral chemotherapy/monoclonal antibodies. Method: Four pharmacists and one pharmacy technician from the oncology hospital (Malta) all participated in eight focus groups linked to the different constructs of Normalisation Process Theory (NPT): coherence, cognitive participation, collective action and reflexive monitoring. The value stream documentation process was mapped by analysing all steps in the process where each activity must add value for the patient; tools of lean thinking were applied. Points causing delay in processing were considered critical; possible changes to minimise time waste were discussed and implemented. Time spent on critical points was measured by timing in minutes each step of the process 1 month before and after the changes had been implemented and calculating the mean±SD. An audit was performed comparing the process with standard operating procedures to determine whether any steps required quality improvement. Results: Three critical points were identified: time required to search for pharmacy patient medication records for chemotherapy/monoclonal antibodies required on the day; time to generate preparation labels; and time to generate worksheets. Overall, a total of 122±8.6 min (p=0.06) were saved per day, a 37% decrease from the original documentation time. Five deficiencies were identified in the documentation process audit; corrective action was proposed. Conclusions: By applying lean thinking, non-value-added steps leading to time waste in the documentation process were eliminated. This concept could be implemented by using NPT as part of a strategic system to reduce waste.